Honey Attenuates the Detrimental Effects of Nicotine on Testicular Functions in Nicotine Treated Wistar Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: Effect of honey on reproductive functions of male rats exposed to nicotine was examined in this study. Thirty-two adult male wistar rats (n=8/Group) were grouped as Control (distilled water), Nicotine (1.0mg/kg bwt), Honey (100mg/kg bwt) and Nicotine with Honey. The animals were orally treated for 35 days consecutively. Epididymis sperm motility, viability, morphology and counts were estimated, serum Follicle Stimulating Hormone (FSH), Leutinizing Hormone (LH) and Testosterone were assayed using ELISA method and testicular histology were also assessed. Significant reduction in percentage sperm motility, viability, morphology and counts were observed in nicotine group (p